The globulin aggregation characteristics induced by salt and alkali and its effects on dough processing quality. (March 2022) - Zhang, Li-Li; Guan, Er-Qi; Yang, Yu-Ling; Zhang, Ting-Jing; Zhang, Yao-Lei; Liu, Yuan-Xiao; Li, Meng-Meng; Zhang, Kai-Ge; Bian, Ke
Abstract: The aggregation characteristics of wheat globulin under NaCl or Na2 CO3 induction were investigated via SDS-PAGE, disulfide bonds analysis, protein secondary structure and surface hydrophobicity. The results showed that both the NaCl and Na2 CO3 treatment promoted the globulin conformation transforming from β-turns and α-helixes to β-sheets and random coils, facilitating the protein aggregation. Moreover, for the NaCl treatment, higher concentrations of NaCl could induce the aggregation of globulin through disulfide bonds. For the Na2 CO3 treatment, disulfide bonds aggregation occurred at a lower concentration; while with the increased concentration, the disulfide bonds were destroyed, and non-disulfide bonds covalent aggregation could be produced. Additionally, the surface hydrophobicity was overall lower, further confirming the massive globulin molecules aggregation. Additionally, following creep and stress relaxation test, it was found that the globulin had an increased impact on the dough elasticity with salt treatment. However, under alkali treatment, the globulin's effects on the dough resistance to deformation and flow, and the stiffness and elasticity of dough were all significantly enhanced. These variation may lie in the aggregation characteristics of globulin analyzed above, which could further enhance the structure of protein network and significantly strengthen the functionality of globulin in dough processing. Graphical abstract: Image 1 Highlights: NaCl treatment (≧500 mM) induced slight aggregation of globulin through S–S linkage. Na2 CO3 (≧500 mM) induced obviously non-disulfide covalent aggregation of globulin. Both NaCl and Na2 CO3 promoted the globulin conformation to a higher level of β-sheets. Na2 CO3 induced reduction of the surface hydrophobicity while NaCl did the opposite. Globulin aggregation strengthened dough quality, especially under Na2 CO3 treatment.